GAMBARAN BULLYING PADA PELAJAR DI KOTA SEMARANG - Kustanti, Erin Ratna (Faculty of Psychology, Diponegoro University, 2015)
The study was aimed to identify bullying behavior in students from various levels of education. This study presented bullying patterns in every level of education like bullying forms, involvement of other parties (friends and teachers) to bullying behavior. The study was conducted to 567 students (95 elementary school students, 200 junior high school students, 134 senior high school students, and 138 college students) The samples were taken from schools and universities located in Tembalang and Banyumanik Semarang. Samples were determined using stratified random sampling technique. Bullying data was obtained from Bullying Experience for Students Questionnaire. The descriptive analysis result concluded that most of students have experienced bullying. Students who receive the most bullying are elementary school students (n = 78; 82.98%). For elementary school students, unpleasant treatments are most often occurs in the classroom and school yard. In college students, unpleasant treatments are most often occurs in the cafeteria and outside the campus. The higher the education level, the percentage of subjects reporting decreases (SD= 60.22%; SMP= 12.36%; SMA= 6.80% dan PT= 5.26%). At all levels of education, most subjects did something when bullying happened to their friend. The percentage of subjects who had conducted bullying a friend at various levels of education is quite high. At the high school level, the percentage is highest, reaching 70%.